Transition metal dichalcogenide (WS2 and MoS2) saturable absorbers for Q-switched Er-doped fiber lasers. (11th April 2018) - Li, Lu; Lv, Ruidong; Liu, Sicong; Wang, Xi; Wang, Yonggang; Chen, Zhendong; Wang, Jiang
Abstract: This report demonstrates a stable Q-switched Er-doped fiber laser with MoS2 (WS2 )-based saturable absorber (SA) in the net normal dispersion regime. The SA is obtained by mixing MoS2 (WS2 ) nanosheets with polyvinyl alcohol (PVA) into polystyrene cells, and then evaporating them to form MoS2 (WS2 )/PVA film. The modulation depth values for MoS2 /PVA and WS2 /PVA are measured to be 2.7% and 2.1% respectively. Employing the MoS2 (WS2 )/PVA film in the Er-doped fiber laser cavity, stable Q-switching operation is achieved with central wavelength of 1560 nm. The shortest pulse durations of the two Q-switched fiber lasers are, respectively, 3.97 and 3.71 µ s, and their maximum single pulse energies are measured to be 131.52 and 126.96 nJ. The experimental results clearly show that MoS2 (WS2 ) is a promising nonlinear material, and that improvements in Q-switching performance due to two SAs in the net normal dispersion regime might be helpful in the design of fiber lasers.